Effect of Processing Parameters on the Microstructure and Corrosion Properties of AlCrFeCoNi High-Entropy Alloy Coatings Fabricated by Laser Cladding - Jingfu Liu; Minghan Bai; Wenjing Xu; Tongjiao Chu (Metals)
AlCrCoFeNi high-entropy alloys (HEAs) have been successfully synthesized by laser cladding. The AlCrFeCoNi HEA coatings were composed of planar crystal, columnar grain, and equiaxed grain from bottom to top. Face-centered cubic (FCC) was the major phase in coatings, and its content decreased when increasing laser power or reducing scanning speed. The precipitation in the HEA coatings were Al-Ni enriched B2 phase and FeAl3 intermetallic compounds. The interface zone had higher microhardness than the cladding zone due to the addition of Fe from the dilution role. The C2 (3 kW, 4 mm/s) and C9 (3.5 kW, 6 mm/s) coatings displayed the best corrosion resistance when taking the Ecorr (−0.327 V, −0.335 V), Icorr (0.236 μA·cm−2, 0.475 μA·cm−2), and Rct (224.2 kΩ/cm2, 121.1 kΩ/cm2) into consideration. Pitting dominated the corrosion process of the AlCrFeCoNi HEA coatings. Large grain boundary areas generated by the fine grain in the C2 and C9 coatings enhanced difficulty of ion transport along the grain boundary. Then, multiple corrosion sites on the surface promoted uniform corrosion and formed a protective oxide film, inhibiting serious pitting. This work provided an approach of laser cladding AlCrCoFeNi HEAs with different laser powers and scanning speeds, and insights into the correlation of anti-corrosion properties with the microstructure of AlCrCoFeNi coatings.